Evaluation of tillage and planting system of upland crops during dry season - Bashar, HMK; Hasan, GN; Sarker, JU; Rahaman, F; Uddin, I (Bangladesh Agronomy Journal, 2015)
Upland crops cultivation in the south central coastal area of Bangladesh is limited due to heavy textured soil with late recession of flood water and early flash flood by heavy rainfall The present study was designed to find out tillage requirement and suitable planting system for upland crops.. Number of tillage (two to four passes) was evaluated along with two planting systems viz., bed and flat planting systems using four crops like, tomato (Solanum lycopersicum L.), brinjal (S. melongena L.), bitter gourd (Momordica charantia L.) and cucumber (Cucumis sativus L.) The crops showed that increased fruit yield with increasing number of tillage in both planting system. But bed planting system produced higher fruit yield (brinjal 67.73 t ha-1, tomato 85.33 t ha-1, bittergourd 41.8 t ha-1 and cucumber 25.8 t ha-1) than flat planting system. Another, bed planting helped to escape crop damage by early heavy rainfall in all crops. Bangladesh Agron. J. 2014, 17(2): 29-37